Analysis of the Technical Efficiency of Castor Farmers in Oyo and Kwara States, Nigeria - Oguntade, Oluwatobi Adebisi; Falola, Abraham; Oguntade, Adegboyega Eyitayo (Journal of Biology and Life Science, 2023)
This study was carried out to evaluate the technical efficiency and production practices of castor farmers in Oyo and Kwara States, Nigeria. Snowballing sampling technique was used. Data on production practices, inputs, and outputs were collected with the aid of a structured questionnaire by trained enumerators and analysed by using data envelopment analysis (DEA). Results showed that the mean technical efficiency was 0.4272 or 42.72%, the maximum efficiency was 1 and the minimum efficiency was 0.1315. Only 14% had a frontier technical efficiency of 1. For the castor farmers to operate on the production frontier, the efficiency needs to be increased by 57.28%. Technically inefficient farms should emulate the operating practices of the most productive farms, to improve their performance. Furthermore, the slacks of the DEA showed that the two most overused variables were seed and labour. The farmers need to use the right quantity of seeds and labour in other to reduce costs without reducing the output. The production practices for castor production were divided into three steps; pre-planting, planting, and post-planting. The list of operations included; land clearing, ploughing, ridging planting, weeding with hoe/machete, herbicide spraying, pesticide spraying, fungicide spraying, fertilizer application, pruning, harvesting, shelling and winnowing. From the study, it can be concluded that if the castor farmers were to operate on the production frontier, the efficiency of input usage would have to increase by 57.28%.